Prevalence and risk factors of cytomegalovirus infection among HIV-infected and HIV-exposed uninfected infants in Nigeria - Emmanuel Ademola Anigilaje; Joseph Othniel Dabit; Nnamdi Okechukwu Nweke; Augustine Aondohemba Agbedeh (Journal of Infection in Developing Countries)
Introduction: Cytomegalovirus (CMV) co-infection increases morbidity and mortality in human immunodeficiency virus (HIV) disease. There has been no study on CMV infection and its risk factors among Nigerian HIV-infected and/or HIV-exposed uninfected infants. Methodology: This was a cross-sectional cohort study at the Federal Medical Center, Makurdi, between January 2012 and March 2013. Acute CMV infection among consecutive three-month- old HIV-infected and HIV-exposed uninfected infants was determined using the enzyme-linked immunosorbent assay of the CMV immunoglobulin M (IgM). The relationship between acute CMV infections in the infants and the potential risk factors was tested using logistic regression analyses. Results: The prevalence of acute CMV infection was 41.4% (91/220), including 12.1% (11/91) and 87.9% (80/91) among the HIV-infected and the HIV-exposed uninfected infants, respectively. In multivariate logistic regression analyses, oropharyngeal candidiasis in the infants, HIV co-infection in the infants, maternal mastitis during breastfeeding, and the absence of maternal chronic CMV infections significantly increased the risk of acute CMV in the young infants. Conclusions: In our setting, concerted efforts to prevent and/or promptly treat oropharyngeal candidiasis and mastitis during breastfeeding may reduce the burden of CMV among HIV-infected and HIV-exposed uninfected infants. Public enlightenment on the mode of CMV transmission and its prevention is also important.